User Awareness of Privacy Concerns Posed by the Use of mHealth Apps (International Journal of Engineering and Computer Science, 2017)
The proliferation of mobile devices such as phones, iPads, tablets, PDAs and other handheld devices, in the society have revolutionised how human activities are carried out today. Jobs and tasks which were erstwhile undertaken only by professionals and specialised institutions within a certain confined environment are now done by individuals who are novices by the mere advantage of owning a mobile device. The health industry is one of the sectors reaping the benefits of this advancement and large number of mobile devices with the applications used on them, mainly Mobile Health Applications. It is observed that this knowledge poses privacy concerns among users of these apps on their mobile devices. Therefore, we propose a research to assess user‟s awareness of their data privacy as it concerns the requesting, collection and usage of their personal information by mHealth applications. We focus on how, when and why these personal data are collected from users in the use of mHealth applications. From our study, it is observed that users, who show indifference concerning their data privacy, have come to know that they can‟t install mobile apps without granting certain permissions. Users‟ nonchalant attitude towards how their personal data are collected and used online is seen in the fact that they say nothing in the User Review section to complain. Also in an online survey conducted most of participant say they review required permissions and apps privacy policies; and read other users‟ review but still installed the apps since they needed to use them. This also affects the adoption of responsible practices by developers. It is argued that had developers seen users showing serious concern over their data privacy they would be more responsible in handling these data during the development of their apps. Non-adoption of responsible research in mHealth apps development places users‟ personal (identity) data at a high risk of mismanagement.